Excellent Service A6 at Grapari Makassar - Tunggul Prasodjo (Jurnal Office, 2021)
Excellent service is closely related to the service business which is carried out in an effort to provide a sense of satisfaction and foster trust in customers or consumers. This study aims to determine the description of excellent service from the A6 aspect in Grapari Makassar. This type of research is a qualitative descriptive study to provide an in-depth picture of excellent service in terms of A6. The informants in this study were five randomly selected customers, and one customer service. Data collection techniques were carried out by interview and observation. The data were analyzed using the Miles, Huberman and Saldana model consisting of data collection, data condensation, data presentation and conclusion drawing. The results of the study indicate that the excellent service from the A6 aspect has been carried out very well